2008
DOI: 10.1161/circulationaha.107.727073
|View full text |Cite
|
Sign up to set email alerts
|

Nix-Mediated Apoptosis Links Myocardial Fibrosis, Cardiac Remodeling, and Hypertrophy Decompensation

Abstract: Background-Pathological cardiac hypertrophy inevitably remodels, leading to functional decompensation. Although modulation of apoptosis-regulating genes occurs in cardiac hypertrophy, a causal role for programmed cardiomyocyte death in left ventricular (LV) remodeling has not been established. Methods and Results-We targeted the gene for proapoptotic Nix, which is transcriptionally upregulated in pressure overload and Gq-dependent hypertrophies, in the mouse germ line or specifically in cardiomyocytes (knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 65 publications
6
138
0
2
Order By: Relevance
“…Among several hundreds of genes that were altered in the heart of Gab1-cKO under TAC conditions, we found that many pro-apoptotic genes, such as Bax (Bcl-2-associated X protein) and Bnip3 (Bcl-2 and adenovirus E1B-19 kDa-interacting protein 3, an apoptotic inducer), 31,32 were upregulated (Supplementary Table S5), whereas several anti-apoptotic genes, including Bcl-2 (B-cell CLL/lymphoma 2) and Egr1 (early growth response 1), were down-regulated (Supplementary Table S6). A major checkpoint in cell death pathway is the ratio of pro-apoptotic (Bax) to anti-apoptotic (Bcl-2) members.…”
Section: Resultsmentioning
confidence: 99%
“…Among several hundreds of genes that were altered in the heart of Gab1-cKO under TAC conditions, we found that many pro-apoptotic genes, such as Bax (Bcl-2-associated X protein) and Bnip3 (Bcl-2 and adenovirus E1B-19 kDa-interacting protein 3, an apoptotic inducer), 31,32 were upregulated (Supplementary Table S5), whereas several anti-apoptotic genes, including Bcl-2 (B-cell CLL/lymphoma 2) and Egr1 (early growth response 1), were down-regulated (Supplementary Table S6). A major checkpoint in cell death pathway is the ratio of pro-apoptotic (Bax) to anti-apoptotic (Bcl-2) members.…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenotype that included hemolytic anemia was subsequently described by two other groups who independently produced NIX/BNIP3L knockout mice (Schweers et al, 2007;Sandoval et al, 2008). Because hematopoietic abnormalities such as these had the potential to confound cardiac studies, a Cre-lox strategy was used to create mice in which the NIX/BNIP3L gene was selectively ablated in cardiac myocytes, which were subjected to surgical transverse aortic constriction (TAC) (Diwan et al, 2008b). This surgical model produces chronic pressure overload that can be modified to the needs of the particular experiment (mild, moderate or severe), and is therefore somewhat analogous to clinical hypertension or valvular aortic stenosis.…”
Section: Transgenic Cardiac Overexpression Studies Of Bnip3 and Nix/bmentioning
confidence: 88%
“…Both proteins are also subject to rapid degradation by the ubiquitin-proteosome pathway (Chen et al, 1999;Cizeau et al, 2000), accounting for barely detectable levels observed in the unstressed myocardium. Importantly, there appears to be no essential physiological or developmental function for either NIX/BNIP3L or BNIP3 in the heart, as cardiac structure and function are normal in the respective cardiac-specific and germ-line gene knockout mouse models (Diwan et al, 2007b(Diwan et al, , 2008b.…”
Section: Cardiomyocyte Apoptosis and Bcl2 Proteins In Myocardial Diseasementioning
confidence: 99%
“…Other Bcl-2 family members such as Bcl-2, Bcl-XL, Bcl-w, Bid, Bim and Puma are also involved in this process (Adams and Cory, 2001). Mitochondrial protein Nix triggers apoptotic cardiomyopathy (Yussman et al, 2002), and Nix overexpression induces cardiomyocyte apoptosis (Diwan et al, 2008).…”
Section: Mitochondria Mediate Apoptosis In Heartmentioning
confidence: 99%